Effect of Molasses Based Multi-nutrient Supplement Containing Chromium on Nutrient Utilization, Milk Yield, Microbial Protein Flow and Antioxidant Status of Lactating Murrah Buffaloes - Patil, Ashok Kumar; Verma, A K; Singh, Putan; Das, Asit (Indian Journal of Animal Nutrition, 2019)
This experiment was conducted to study the effect of supplement Molasses based multi-nutrients containing chromium Picolinate on nutrient utilization, milk yield, microbial protein flow and antioxidant status of lactating Murrah buffaloes. Thus 21 lactating buffaloes were equally divided into three groups (n=7) on the basis of body weight and milk yield. Basal diet consisting wheat straw, maize green and concentrate mixture were fed to all groups. In addition to basal diet, the animals of group T2 fed 250 g Molasses based multi-nutrients supplement (MMS-1) and group T3 fed with 250 g MMS plus 5 mg Chromium Picolinate (MMS-2) . The digestibilities of the nutrients remained uninfluenced (P>0.05) among all the groups. Dietary MMS supplementation tended to improvement in milk yield by 18 (T2) and 16 (T3) percent. The activities of superoxide dismutase, catalase and glutathione peroxidase were significantly (P<0.05) higher in both the supplemented groups, however, the mean value of glutathione reductase was similar in all three groups. It was found that MMS supplementation did not have any significant effect on urinary excretion of allantoin, uric acid, purine derivative, creatinine and PDC index (mmol/l) among all the groups. From the results it can be deduced that supplementation of molasses based multi-nutrients (250 g/buffalo/day) improved milk yield by 18 (T2) and 16 (T3) percent and had better antioxidant status with comparable intake and digestibility of nutrients in lactating Murrah buffaloes.